1987
DOI: 10.1002/mrd.1120180107
|View full text |Cite
|
Sign up to set email alerts
|

Binding of morphologically abnormal sperm to mouse egg zonae pellucidae in vitro

Abstract: The ability of morphologically abnormal mouse sperm to bind to the zona pellucida of the egg was examined with techniques of fertilization in vitro. After incubation with sperm, cumulus-free ova were scored by either phase microscopy or scanning electron microscopy for the number and type of sperm bound. The percentages of abnormal sperm bound to zonae were compared to the percentages of abnormal sperm in the inseminating suspension. In general, all abnormal classes (except broadly spatulate sperm) bound to zo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
3
1

Year Published

1990
1990
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 11 publications
0
28
3
1
Order By: Relevance
“…However, when the percentage of abnormal spermatozoa was very high in the insemination medium, no significant difference existed between frequencies of abnormal spermatozoa bound to the ZP and in the insemination medium (Kot & Handel, 1987). In the present study, using the conventional method for assessing spermatozoal morphology under 1000 magnification with oil immersion, we found that abnormal spermatozoa bind to the ZP at significantly lower rates than normal spermatozoa.…”
Section: Discussioncontrasting
confidence: 66%
“…However, when the percentage of abnormal spermatozoa was very high in the insemination medium, no significant difference existed between frequencies of abnormal spermatozoa bound to the ZP and in the insemination medium (Kot & Handel, 1987). In the present study, using the conventional method for assessing spermatozoal morphology under 1000 magnification with oil immersion, we found that abnormal spermatozoa bind to the ZP at significantly lower rates than normal spermatozoa.…”
Section: Discussioncontrasting
confidence: 66%
“…The homozygosity for azh mutation has a dramatic effect on male fecundity, yielding males that are almost completely infertile [15,16]. It was reported that spermatozoa from azh/azh mice failed in binding to the zona pellucida [19], which suggested that the major cause of infertility in azh/azh mice is at the level of binding and penetration of the zona pellucida. It was later shown that mice homozygous for azh mutation were unable to fertilize intact oocytes but were able to fertilize zona-free eggs [20].…”
Section: Introductionmentioning
confidence: 99%
“…The proportion varies depending upon the species or the strains (Beatty & Sharma, 1960;Beatty, 1972; Wyrobek, 1979;Krzanowska, 1981), from 4% in SW mice (Wyrobek et ai, 1975;Pogany, 1987) to 99% in the azh/azh strain (Kot & Handel, 1987). The mechanisms responsible for nuclear deformation in these cells are not understood, but deformed spermatozoa are known to penetrate the zona pellucida of oocytes in vitro (Kot & Handel, 1987) and to fertilize eggs (Moore Smith, 1970; Krzanowska & Lorenc, 1983). Deformed spermatozoa may also contribute to reproductive dysfunctions and are suspected to cause habitual abortions (Giarola & Ballerio, 1962).…”
Section: Introductionmentioning
confidence: 99%